Spatio-temporal Variation of Sediment Methanotrophic Microorganisms in a Large Eutrophic Lake - Yang, Yuyin; Zhao, Qun; Cui, Yahui; Yilin Wang; Xie, Shuguang; Yong Liu (MICROBIAL ECOLOGY, 2016)
Aerobic methane-oxidizing bacteria (MOB) play a crucial role in mitigating the methane emission from lake ecosystems to the atmosphere. However, the distribution of methanotrophic community in shallow and eutrophic lake and its influential factors remain essentially unclear. The present study investigated sediment methanotrophic microorganisms at different sites in eutrophic freshwater Dianchi Lake (China) in two different seasons. The abundance, diversity, and structure of sediment methanotrophic community showed a profound spatial and seasonal variation. The pmoA gene copy number in lake sediments ranged from 8.71 +/- 0.49 x 10(4) to 2.09 +/- 0.03 x 10(7) copies per gram of dry sediment. Sediment methanotrophic communities were composed of Methylococcus and Methylobacter (type I methanotrophs) and Methylosinus (type II methanotrophs), while type I MOB usually outnumbered type II MOB. Moreover, ammonia nitrogen was found to be a potential determinant of methanotrophic community structure in Dianchi Lake.